Improving Web Search Results Using Affinity Graph - Zhang, Benyu; Li, Hua; Liu, Yi; Ji, Lei; Xi, Wensi; Fan, Weiguo; Chen, Zheng; Ma, Wei-Ying (28th annual international ACM SIGIR conference on Research and development in informaion retrieval, 2005)
In this paper, we propose a novel ranking scheme named Affinity Ranking (AR) to re-rank search results by optimizing two metrics: (1) diversity – which indicates the variance of topics in a group of documents; (2) information richness – which measures the coverage of a single document to its topic. Both of the two metrics are calculated from a directed link graph named Affinity Graph (AG). AG models the structure of a group of documents based on the asymmetric content similarities between each pair of documents. Experimental results in Yahoo! Directory, ODP Data, and Newsgroup data demonstrate that our proposed ranking algorithm significantly improves the search performance. Specifically, the algorithm achieves 31% improvement in diversity and 12% improvement in information richness relatively within the top 10 search results.